Memaknai Kode Etik Dalam Meningkatkan Profesionalisme Seorang Guru PAK Mengajar Bagi Peserta Didik - Diana Hartatina Harefa; Yosia Belo (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
The Code of Ethics is very important for the professionalism of an PAK teacher in carrying out the learning process and advancing the world of education. The quality of a student in the world of education is very dependent on the quality of a teacher. Therefore, a PAK teacher who is professional should have competence in accordance with national education standards so that he can carry out his duties and roles with good competency standards, which results in students becoming knowledgeale human beings and possessing skills. Not only that, before educating a PAK teacher, he must be equipped with the values of truth that are in accordance with god’s word. Being a teacher is not only as a teacher but as a guide for the character of students to become characters that are pleasing to the lord jesus. A PAK teacher before educating is able to study the teachers code of ethics well according to a Biblical perspective. If an PAK teacher can master and understand the correct code of ethics then in every teaching and guidance that is done to students it can run according to the truth of God’s Word.